A pediatric case of T‐cell prolymphocytic leukemia. Issue 6 (21st November 2014) - Mitton, Bryan; Coutre, Steven; Willert, Jennifer; Schlis, Krysta; Porteus, Matthew; Kharbanda, Sandhya; Agarwal‐Hashmi, Rajni
<x xml:space="preserve">Abstract</x> T‐cell Prolymphocytic Leukemia (T‐PLL) is a rare entity, and to date has never been reported in children. Here, we describe the first pediatric case of T‐PLL in a 16‐year old male and review his clinical course through treatment. He underwent therapy with alemtuzumab and pentostatin, which was successful in inducing initial remission. He then underwent an allogeneic matched sibling stem cell transplant following a myeloablative conditioning regimen and remains disease‐free 1.5 years after diagnosis. Pediatr Blood Cancer 2015;62:1061–1062. © 2014 Wiley Periodicals, Inc.